Resource partitioning among air-breathing marine predators: are body size and mouth diameter the major determinants? - Saporiti, Fabiana (2016)
Although the body size of consumers may be a determinant factor in structuring food webs, recent evidence indicates that body size may fail to fully explain differences in the resource use patterns of predators in some situations. Here we compared the trophic niche of three sympatric and sexually dimorphic airbreathing marine predators (the South American sea lion, Otaria flavescens, the South American fur seal, Arctocephalus australis, and the Magellanic penguin, Spheniscus magellanicus) in three areas of the Southwestern Atlantic Ocean (R ıo de la Plata and adjoining areas, Northern Patagonia and Southern Patagonia), in order to assess the importance of body size and mouth diameter in determining resource partitioning. Body weight and palate/bill breadth were used to characterize the morphology of each sex and species, whereas the trophic niche was assessed through the use of stable isotope ratios of carbon and nitrogen. The quantitative method Stable Isotope Bayesian Ellipses in R (SIBER) was used to compute the area of the Bayesian ellipses and the overlap of the isotopic niches. The results showed that morphological similarity was significantly correlated with isotopic distance between groups within the d13C– d15N bi-plot space in the R ıo de la Plata area, but not in Northern and Southern Patagonia. Furthermore, resource partitioning between groups changed regionally, and some morphologically distinct groups exhibited a large trophic overlap in certain areas, such as the case of male penguins and male sea lions in Southern Patagonia. Conversely, female sea lions always overlapped with the much larger males of the same species, but never overlapped with the morphologically similar male fur seals. These results indicate that body size and mouth diameter are just two of the factors involved in resource partitioning within the guild of air-breathing predators considered here, and for whom – under certain environmental conditions – other factors are more important than morphology.